Hadith #3943 - Sahih Muslim - Habib al-Ma'lm Abu Muhammad حبيب المعلم أبو محمد البصري (Sahih Muslim)
I asked al-Bara’ b. Azib about the exchange of (gold for silver or vice versa), whereupon he said: you better ask Zaid b. Arqam for he knows more than I. So I asked Zaid but he said: You better ask al-Bara’ for he knows more than I. Then both of them said: Allah’s Messenger (ﷺ) forbade the sale of silver for gold when payment is to be made in future.
Grade: Sahih

Hadith #74 - Sunan al-Nasa'i - Abbad bin Tameem Mazni; Habib al-Ma'lm Abu Muhammad حبيب المعلم أبو محمد البصري; Muhammad bin Bashar Bindar محمد بن بشار بندار; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan al-Nasa'i)
“I heard ‘Abbad bin Tamim narrate from my grandmother – who was Umm ‘Umarah bint Ka’b – that the Prophet (ﷺ) performed Wudu’, and he was brought a vessel in which there were two-thirds of a Mudd.” Shu’bah said: “I remember that he washed his forearms and started rubbing them, and he wiped the inside of his ear, but I do not remember whether he wiped the outside of them.”
Grade:

Hadith #632 - Sunan al-Nasa'i - al-Dahhak bin Mukhlad Abu 'Asim al-Nabil الضحاك بن مخلد أبو عاصم النبيل; Amr bin Hrm al-Azdy عمرو بن هرم الأزدي البصري; Habib al-Ma'lm Abu Muhammad حبيب المعلم أبو محمد البصري; Hiban bin Hilal حبان بن هلال; ibn Abbas; Jabir bin Zayd al-Azdi جابر بن زيد الأزدي (Sunan al-Nasa'i)
It was narrated from Abu Mahdhurah that the Messenger of Allah (S.A.W) taught him the Adhan with nineteen phrases and the Iqamah with seventeen phrases, then Abu Mahdhurah counted them as nineteen and seventeen.
Grade:

Hadith #1667 - Sunan al-Nasa'i - Habib al-Ma'lm Abu Muhammad حبيب المعلم أبو محمد البصري; ibn Umar; Jarir bin 'Abdul Hameed al-Razi جرير بن عبد الحميد أبو عبد الله الضبي; Mansur bin al-Ma'tamar al-Salmi منصور بن المعتمر بن عبد الله السلمي; Tawus bin Kaysan طاوس (Sunan al-Nasa'i)
“I asked Aishah: “How did the Messenger of Allah (ﷺ) recite at night- did he recite loudly or silently?” She said: ‘He used to do both; sometimes he recited loudly and sometimes he recited silently.'”
Grade:

Hadith #2031 - Sunan al-Nasa'i - Ali ibn Abi Talib; Amr bin 'Ali bin Bahr al-Bahli عمرو بن علي بن بحر الباهلي; Habib al-Ma'lm Abu Muhammad حبيب المعلم أبو محمد البصري; Shaqayq bin Salmah al-Asadi شقيق بن سلمة الأسدي أبو وائل الكوفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan al-Nasa'i)
“The Messenger of Allah went our to the funeral of Ibn Ad-Dahdah, and when he came back an unsaddled horse was brought to him, so he rode and we walked with him.”
Grade:

Hadith #2398 - Sunan al-Nasa'i - Abdullah bin 'Amr bin al-'Aas; Ali bin al-Husain bin 'Ali علي بن الحسين بن علي - زين العابدين; Habib al-Ma'lm Abu Muhammad حبيب المعلم أبو محمد البصري; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan al-Nasa'i)
“I entered upon ‘Abdullah bin ‘Amr and said: O uncle, tell me what the Messenger of Allah said to you. He said: O son of my brother, I had resolved to strive very hard until I said: I will fast for the rest of my life and I will read the whole Quran every day and night. The Messenger of Allah heard about that, and came in to me in my house, and said: I have heard that you said, I will fast for a lifetime and will read the Quran. I said: I did say that, O Messenger of Allah. He said; Do not
Grade:

Hadith #2765 - Sunan al-Nasa'i - Amr bin Hrm al-Azdy عمرو بن هرم الأزدي البصري; Habib al-Ma'lm Abu Muhammad حبيب المعلم أبو محمد البصري; Harun bin 'Abdullah al-Hamal هارون بن عبد الله بن مروان الحمال; ibn Abbas; Ikrama عكرمة; Sa'id bin Jubayr سعيد بن جبير الأسدي; Sulaiman bin Da'ud bin al-Jarud سليمان بن داود أبو داود الطيالسي (Sunan al-Nasa'i)
“I said to Ibn ‘Umar: ‘I saw you begin the Talbiyah when your she-camel stood up with you. He said: “The Messenger of Allah used to begin the Talbiyah when his she-camel stood up with him.”
Grade:

Hadith #3056 - Sunan al-Nasa'i - Abdur Rahman bin Mahdi عبد الرحمن بن مهدي; Habib al-Ma'lm Abu Muhammad حبيب المعلم أبو محمد البصري; ibn Abbas; Muhammad bin Bashar Bindar محمد بن بشار بندار; Sa'id bin Jubayr سعيد بن جبير الأسدي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan al-Nasa'i)
“I came with Asma bint Abi Bakr to Mina at the end of the night and I said to her: ‘We have come to Mina at the end of the night.’ She said: ‘We sued to do this one who was better than you.'”
Grade:

Hadith #3065 - Sunan al-Nasa'i - Ata' bin Abi Rabah عطاء بن أبي رباح; Bashr bin al-Sari al-Afwah بشر بن السري أبو عمرو الأفوه; Habib al-Ma'lm Abu Muhammad حبيب المعلم أبو محمد البصري; ibn Abbas; Mahmud bin Ghaylan محمود بن غيلان العدوي مولاهم أبو أحمد; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan al-Nasa'i)
“On the morning of Al-Aqabah, while he was on his mount, the Messenger of Allh said: ‘Pick up (some pebbles) for me.’ So P picked up some pebbles for him that were the size of date stones of fingertips, and placed them in his hand. He started to do this with his hand.” Yahya described him shaking them in his hand like this.
Grade:

Hadith #4214 - Sunan al-Nasa'i - Affan bin Muslim عفان بن مسلم بن عبد الله الصفار; Ayoub al-Sakhtiyani أيوب السختياني; Habib al-Ma'lm Abu Muhammad حبيب المعلم أبو محمد البصري; Hammad bin Salama حماد بن سلمة; Ibn Sirin محمد بن سيرين الأنصاري; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن; Qatada قتادة; Yonus bin Yazid bin Abi al-Nijad يونس بن يزيد بن أبي النجاد (Sunan al-Nasa'i)
” I heard my paternal aunt say: ‘The Messenger of Allah said; “Whoever among you is appointed to a position of authority. If Allah wills good for him. He will give him a righteous minister who will remind him if he forgets and help him if he remembers
Grade:

Hadith #4577 - Sunan al-Nasa'i - al-Bara' bin Azib bin al-Harith; Habib al-Ma'lm Abu Muhammad حبيب المعلم أبو محمد البصري; Muhammad bin 'Ubaid al-Tanafasi محمد بن عبيد بن أبي أمية الطنافسي; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Siyar bin Salaama, Abu al-Minhal سيار بن سلامة الرياحي أبو المنهال (Sunan al-Nasa'i)
“Dinar for Dinar Dirham for Dirham, no difference between them.”
Grade:

Hadith #5550 - Sunan al-Nasa'i - Abdullah bin Numayr عبد الله بن نمير; Abu Sa'id al-Khudri; al-Husain bin Mnswr bin Ja'far الحسين بن منصور بن جعفر; Habib al-Ma'lm Abu Muhammad حبيب المعلم أبو محمد البصري; Sulaiman al-A'mash الأعمش / سليمان بن مهران (Sunan al-Nasa'i)
“While I was taking care of a group of people, including my paternal uncles, and I was the youngest of them, a man came and said: ‘Khamr has been forbidden.’ I was taking care of them, and was pouring Fadikh (date-wine) for them. They said: ‘Pour it away.’ So I poured it away.” I (the narrator) said to Anas: “What is that?” He said: “Unripe dates and dried dates.” Abu Bakr bin Anas said: “That was their wine in those days.” And Anas did not deny that.
Grade:

Hadith #2396 - Sunan Abi Dawud - Abu Hurairah; Ahmad bin Hanbal أحمد بن حنبل; Ammara bin al-Q'aqa' bin Shabrma عمارة بن القعقاع بن شبرمة; Habib al-Ma'lm Abu Muhammad حبيب المعلم أبو محمد البصري; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
The Prophet (ﷺ) said: If anyone breaks his fast one day in Ramadan without a concession granted to him by Allah, a perpetual fast will not atone for it.
Grade: Da'if

Hadith #2397 - Sunan Abi Dawud - Abu Hurairah; Ayoub al-Sakhtiyani أيوب السختياني; Habib al-Ma'lm Abu Muhammad حبيب المعلم أبو محمد البصري; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Hisham bin 'Urwa هشام بن عروة; Ibn Sirin محمد بن سيرين الأنصاري; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي (Sunan Abi Dawud)
Sufyan and Shu’bah differed among themselves on the name of the narrator Ibn al-Mutawwas and Abu al-Mutawwas.
Grade: Da'if

Hadith #2856 - Sunan Abi Dawud - Amr bin Shu'aib bin Muhammad عمرو بن شعيب بن محمد السهمي; Habib al-Ma'lm Abu Muhammad حبيب المعلم أبو محمد البصري; Muhammad bin al-Minhal al-Darir محمد بن المنهال الضرير; Shu'aib bin Muhammad bin 'Abdullah شعيب بن محمد بن عبد الله بن عمرو; Yazid bin Zari' يزيد بن زريع (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) said to me: AbuTha’labah, eat what returns to you by your bow and your dog. Ibn Harb’s version adds: “The trained (dog), and your hand, then eat, whether it has been slaughtered or not slaughtered”.
Grade: Sahih

Hadith #2910 - Sunan Abi Dawud - Abdullah bin 'Amr bin al-'Aas; Amr bin Shu'aib bin Muhammad عمرو بن شعيب بن محمد السهمي; Habib al-Ma'lm Abu Muhammad حبيب المعلم أبو محمد البصري; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي; Shu'aib bin Muhammad bin 'Abdullah شعيب بن محمد بن عبد الله بن عمرو (Sunan Abi Dawud)
I said: Messenger of Allah, where will you stay tomorrow ? This (happened) during his Hajj. He replied: Has ‘Aqil left any house for us ? He then said: We shall stay at the valley of Banu Kinarah where the Quraish took an oath on unbelief. This refers to al-Muhassab. The reason is that Banu Kinarah made an alliance with the Quraish against Banu Hashim that they would have no marital connections with them, nor will have commercial transactions with them, not will give them any refuge. Al-Zuhri
Grade: Sahih

Hadith #3271 - Sunan Abi Dawud - Amr bin Shu'aib bin Muhammad عمرو بن شعيب بن محمد السهمي; Habib al-Ma'lm Abu Muhammad حبيب المعلم أبو محمد البصري; Muhammad bin al-Minhal al-Darir محمد بن المنهال الضرير; Sa'id ibn al-Musayyib سعيد بن المسيب بن حزن أبو محمد القرشي; Yazid bin Zari' يزيد بن زريع (Sunan Abi Dawud)
“Expiation (for breaking the oath) has not reached me.”
Grade: Sahih

Hadith #3304 - Sunan Abi Dawud - Ata' bin Abi Rabah عطاء بن أبي رباح; Habib al-Ma'lm Abu Muhammad حبيب المعلم أبو محمد البصري; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي (Sunan Abi Dawud)
Uqbah said to the Prophet (ﷺ): My sister has taken a vow that she will walk to the House of Allah (the Ka’bah). Thereupon he said: Allah will not do anything of the walking of your sister to the House of Allah (i.e. the Ka’bah).
Grade: Sahih

Hadith #3443 - Sunan Abi Dawud - Abu Hurairah; Ayoub al-Sakhtiyani أيوب السختياني; Habib al-Ma'lm Abu Muhammad حبيب المعلم أبو محمد البصري; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Hisham bin 'Urwa هشام بن عروة; Ibn Sirin محمد بن سيرين الأنصاري; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) as saying: Do not go out to meet riders to conduct business with them ; none of you must buy in opposition to one another; and do not tie up the udders of camels and sheep, for he who buys them after that has been done has two courses open to him after milking them: he may keep them if he is pleased with them, or he may return them along with a sa’ of dates is he is displeased with them.
Grade: Sahih

Hadith #3529 - Sunan Abi Dawud - Amr bin Shu'aib bin Muhammad عمرو بن شعيب بن محمد السهمي; Habib al-Ma'lm Abu Muhammad حبيب المعلم أبو محمد البصري; Muhammad bin al-Minhal al-Darir محمد بن المنهال الضرير; Shu'aib bin Muhammad bin 'Abdullah شعيب بن محمد بن عبد الله بن عمرو; Yazid bin Zari' يزيد بن زريع (Sunan Abi Dawud)
The Prophet (ﷺ) Said: The children of a man come from what he earns, rather they are his pleasantest earning; so enjoy from their property. Abu Dawud said: Hammad b. Abi Sulaiman added in his version: “When you need.” But this (addition) is munkar (not authoritative).
Grade: Sahih

Hadith #3545 - Sunan Abi Dawud - Amr bin Shu'aib bin Muhammad عمرو بن شعيب بن محمد السهمي; Da'ud bin Abi Hnd داود بن أبي هند; Habib al-Ma'lm Abu Muhammad حبيب المعلم أبو محمد البصري; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي; Shu'aib bin Muhammad bin 'Abdullah شعيب بن محمد بن عبد الله بن عمرو (Sunan Abi Dawud)
Bashir’s wife said (to her husband): Give my son your slave, and call the Messenger of Allah (ﷺ) as witness for me. So he came to the Messenger of Allah (ﷺ) and said: The daughter of so-and-so has asked me to give her som my slave and said to me: Call the Messenger of Allah (ﷺ) as witness for her. He asked: Has he brothers? He replied: Yes. He again asked: Has he given them all the same as you have given him? He replied: No. He said: This is not good, and I will be a witness to what it r
Grade: Sahih

Hadith #4907 - Sunan Abi Dawud - Aisha bint Abi Bakr; Ata' bin Abi Rabah عطاء بن أبي رباح; Habib al-Ma'lm Abu Muhammad حبيب المعلم أبو محمد البصري; Mua'dh bin Mua'dh bin Nsr معاذ بن معاذ بن نصر; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Ubaidullah bin Mua'dh عبيد الله بن معاذ بن معاذ بن نصر (Sunan Abi Dawud)
I heard the Messenger of Allah (May peace be upon him) say: Men given to cursing will not be witnesses or intercessors.
Grade: Sahih

Hadith #5187 - Sunan Abi Dawud - Abu Hurairah; Habib al-Ma'lm Abu Muhammad حبيب المعلم أبو محمد البصري; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Hisham bin 'Urwa هشام بن عروة; Ibn Sirin محمد بن سيرين الأنصاري; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي (Sunan Abi Dawud)
I knocked at the door. He asked : who is there? I replied: it is I. he said: I, as though he disapproved of it.
Grade: Sahih

Hadith #923 - Jami' al-Tirmidhi - Aisha bint Abi Bakr; Habib al-Ma'lm Abu Muhammad حبيب المعلم أبو محمد البصري; Hisham bin 'Urwa هشام بن عروة; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Urwa ibn al-Zubayr عروة بن الزبير; Yazid bin Zari' يزيد بن زريع (Jami' al-Tirmidhi)
“At-Tahsib is nothing, it is only a place that the Messenger of Allah camped at.”
Grade:

Hadith #2048 - Jami' al-Tirmidhi - al-Fadl bin Dakayn, Abu Na'eem الفضل بن دكين أبو نعيم الملائي; Habib al-Ma'lm Abu Muhammad حبيب المعلم أبو محمد البصري; Mahmud bin Ghaylan محمود بن غيلان العدوي مولاهم أبو أحمد; Muhammad bin 'Abdullah bin al-Zubair محمد بن عبد الله أبو أحمد الزبيري; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Jami' al-Tirmidhi)
“Indeed the best of what you treat is As-Sa’ut, Al-Ladud, cupping and laxatives.’ And the best of what you use for Kuhl is Ithmid, for it clears the vision and grows the hair (eye-lashes).” And he said:” The Messenger of Allah (s.a.w) had a Kuhl holder with which he would apply Kuhl before sleeping three in each eye.”
Grade:

Hadith #3712 - Sunan Ibn Majah - Abdul Warith bin Sa'id bin Dhakwan عبد الوارث بن سعيد بن ذكوان; Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Abu Hurairah; Affan bin Muslim عفان بن مسلم بن عبد الله الصفار; Aisha bint Abi Bakr; Habib al-Ma'lm Abu Muhammad حبيب المعلم أبو محمد البصري (Sunan Ibn Majah)
“The best lifestyle is that of a man who holds onto the reins of his horse for the sake of Allah, riding on its back. Every time he hears a commotion he rushes towards it, seeking death wherever he thinks he can find it; and a man who tends sheep at the top of one of these peaks, or in the bottom of one of these valleys, establishing the prayer, paying the charity, and worshipping his Lord until the inevitable (death) comes to him and there is nothing between him and the people except good.”
Grade: